Use and reporting of experience-based codesign studies in the healthcare setting: a systematic review. Issue 1 (23rd September 2019) - Green, Theresa; Bonner, Ann; Teleni, Laisa; Bradford, Natalie; Purtell, Louise; Douglas, Clint; Yates, Patsy; MacAndrew, Margaret; Dao, Hai Yen; Chan, Raymond Javan
Abstract : Background: Experience-based codesign (EBCD) is an approach to health service design that engages patients and healthcare staff in partnership to develop and improve health services or pathways of care. The aim of this systematic review was to examine the use (structure, process and outcomes) and reporting of EBCD in health service improvement activities. Methods: Electronic databases (MEDLINE, CINAHL, PsycINFO and The Cochrane Library) were searched to identify peer-reviewed articles published from database inception to August 2018. Search terms identified peer-reviewed English language qualitative, quantitative and mixed methods studies that underwent independent screening by two authors. Full texts were independently reviewed by two reviewers and data were independently extracted by one reviewer before being checked by a second reviewer. Adherence to the 10 activities embedded within the eight-stage EBCD framework was calculated for each study. Results: We identified 20 studies predominantly from the UK and in acute mental health or cancer services. EBCD fidelity ranged from 40% to 100% with only three studies satisfying 100% fidelity. Conclusion: EBCD is used predominantly for quality improvement, but has potential to be used for intervention design projects. There is variation in the use of EBCD, with many studies eliminating or modifying some EBCD stages. Moreover, there is no consistency in reporting. In order to evaluate the effect of modifying EBCD or levels of EBCD fidelity, the outcomes of each EBCD phase (ie, touchpoints and improvement activities) should be reported in a consistent manner. Trial registration number: CRD42018105879.